Tradisi Tari Ngebeng Dalam Perspektif Hukum Islam: Studi Kasus di Desa Rambutan Masam Kecamatan Muara Tembesi Kabupaten Batanghari - Ahmad Januarsyah; Iliyanti Iliyanti; Husein Bafadhal (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The background to the problem of this research is looking at the habits of the people of Rambutan Masam Village, which to this day still preserve the tradition of the Ngebeng Dance, where the dance shows men dancing in a bancian style, plus the costumes and make-up of the men are really made to resemble Woman. The main problem in this research is: what is the process of implementing the Ngebeng Dance tradition in Rambutan Masam Village, and what is the perspective of Islamic law on this problem.This research is a field research conducted in Rambutan Masam Village. The population is several people who understand the history of the ngebeng dance, such as heads of traditional institutions, community leaders, while the sampling technique used was purposive sampling, namely 10 people who were directly involved. in the implementation of the ngebeng tradition and the researchers interviewed directly. Because to get data in the field it is collected by observation and interviews. Next in analyzing. The data writer used an empirical juridical approach method, because in discussing the research problem he used legal materials, both written and unwritten laws or both primary legal materials and secondary legal materials.The results of the research show that the process of implementing the ngebeng dance tradition is still preserved to this day and still maintains the content of the dance as taught by the ancestors, where men in the dance are dressed in such a way as to resemble women. So this dance tradition according to Islamic law is haram even though it aims to entertain.